2010
DOI: 10.1007/s12975-010-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperglycemia on Brain Penetrating Arterioles and Cerebral Blood Flow Before and After Ischemia/Reperfusion

Abstract: The effect of preexisiting hyperglycemia on cerebral blood flow (CBF) and brain penetrating arterioles before and after 2 h of ischemia and 30 min of reperfusion was determined. Male Wistar rats that were either hyperglycemic (50 mg/kg streptozotocin; n=24) or normoglycemic (n=24) were subjected to transient ischemia by filament occlusion or nonischemic. CBF was measured prior to ischemia using microspheres and during transient ischemia using laser Doppler. Edema was compared by wet/dry weights. Constriction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…The mechanism of the effects of hyperglycaemia on lacunar stroke is not yet known. Experiments have also found that the effect of ischaemia was not different between normoglycaemic and hyperglycaemic animals with end-artery infarcts, 27,28 suggesting that it was related to ischaemia and reperfusion rather than to hyperglycaemia. However, in subcortical strokes, the magnetic resonance spectroscopy also provided evidence of metabolically compromised area.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism of the effects of hyperglycaemia on lacunar stroke is not yet known. Experiments have also found that the effect of ischaemia was not different between normoglycaemic and hyperglycaemic animals with end-artery infarcts, 27,28 suggesting that it was related to ischaemia and reperfusion rather than to hyperglycaemia. However, in subcortical strokes, the magnetic resonance spectroscopy also provided evidence of metabolically compromised area.…”
Section: Discussionmentioning
confidence: 98%
“…Basal tone was reduced in both normoglycemic and hyperglycemic animals to the same degree suggesting that it was due to ischemia/reperfusion injury and independent of glucose. They also demonstrated that acute hyperglycemia had no effect on endothelium dependent vasodilator production in penetrating arterioles which may explain why lacunar strokes are not worsened by hyperglycemia [71]. However, studies done on cortical stroke revealed a deleterious effect of acute hyperglycemia on vascular reactivity.…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Blood gases and pH were maintained within normal ranges (Table 1). CBF was continuously measured using laser Doppler flowmetry (Perimed Periflux 5010 Laser Doppler System, North Royalton, OH, USA), as previously described (Cipolla et al, 2001;Cipolla and Godfrey, 2010). Briefly, the flow probe was affixed over a thinned area of skull posterior to the coronal suture and lateral to the sagittal suture over the MCA perfusion domain.…”
Section: Peroxynitrite Decomposition Catalyst Treatmentmentioning
confidence: 99%